PENINGKATAN PEMAHAMAN SISWA SMPN 2 BLAHBATUH KABUPATEN GIANYAR TENTANG KONSERVASI BENDA CAGAR BUDAYA MELALUI UPAYA PENDIDIKAN DAN PELATIHAN - AGUNG BAWONO.R; UFI NAJIB; N. K.PUJI ASTITI LAKSMI; ZURAIDAH ZURAIDAH; KRISTIAWAN KRISTIAWAN; C. PALUPI TITASARI (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2009)
ABSTRACT The improvement of comprehension about cultural heritage and conservation to the young generations can be done by education and training. The methods applied are presentation with discussion and training of conservation. The advantage of comprehension signification about cultural heritage is indicated by the improving percentage from 30 students (81.08%) became 37 students (100%), about rescuing of cultural heritage from 36 students (97.89%) became 37 students (100%), about conservation from 15 students (40.54%) became 34 students (91.89%). And for conservation technique become 34 students (91.89%) from 5 students (13.52%). The result shows that technics of education and training is efective for advance students in comprehending the cultural hetitage and conservation techniques.